Factors Driving Stock Prices of Nepalese Insurers - Karki, Dipendra (NCC Journal, 2020)
The effect of firm-specific and macroeconomic factors on the price-earnings ratio of Nepalese insurance companies is analyzed in this study using pooled cross-sectional data. The study covers a period of eight years (2007/08 to 2014/15) and uses secondary data from 13 insurance companies with a total of 104 observations. The findings suggest that firm size, money supply, and gross domestic product have a positive correlation with stock prices, while inflation has a negative correlation. Furthermore, size, gross domestic product, and money supply have a positive impact on the price-earnings ratio, whereas dividends per share, book value per share, return on equity, and inflation have a negative impact. The study's results have important implications for insurance companies in Nepal, particularly in making investment decisions and formulating pricing strategies. The research's analytical techniques and strategies can be applied to different facets of the Nepalese stock market.